MiR-146a encapsulated liposomes reduce vascular inflammatory responses through decrease of ICAM-1 expression, macrophage activation, and foam cell formation. Issue 7 (26th January 2023) - Ho, Donald; Lynd, Tyler O.; Jun, Claire; Shin, Juhee; Millican, Reid C.; Estep, Benjamin K.; Chen, Jun; Zhang, Xixi; Brott, Brigitta C.; Kim, Dong Woon; Sherwood, Jennifer A.; Hwang, Patrick T. J.
Abstract : Treatment of microRNA-146a encapsulated liposomes reduces vascular inflammation by targeting multiple related components including endothelial cell, smooth muscle cell, and macrophage activation as well as foam cell formation. Abstract : Vascular insults can create an inflammatory cascade involving endothelial cell, smooth muscle cell, and macrophage activation which can eventually lead to vascular disease such as atherosclerosis. Several studies have identified microRNA 146a's (miR-146a) anti-inflammatory potential based on its role in regulating the nuclear factor kappa beta (NF-κβ) pathway. Therefore, in this study, we introduced exogenous miR-146a encapsulated by liposomes to lipopolysaccharide (LPS) stimulated vascular cells and macrophages to reduce inflammatory responses. First, the miR-146a encapsulated liposomes showed uniform size (radius 96.4 ± 4.22 nm) and round shape, long term stability (at least two months), high encapsulation efficiency (69.73 ± 0.07%), and were well transfected to human aortic endothelial cells (HAECs), human aortic smooth muscle cells (SMCs), and human differentiated monocytes (U937 cells). In addition, we demonstrated that miR-146a encapsulated liposomes reduced vascular inflammation responses in HAECs and SMCs through inhibition of ICAM-1 expression and decreased monocyte adhesion. In macrophages, miR-146a liposome treatment demonstrated decreased production of proinflammatory cytokines, tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β), as well as reduced oxidized low-density lipoprotein (ox-LDL) uptake and foam cell formation. Thus, based on these results, miR-146a encapsulated liposomes may be promising for reducing vascular inflammation by targeting its multiple associated mediators.